2008
DOI: 10.1111/j.1600-0870.2008.00307.x
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of cyclones in the ARPEGE general circulation model

Abstract: Baroclinic waves give major contributions to the climatology and variability of key climate variables in mid‐ and high‐latitudes. An important aspect of cyclone variability is the seriality (succession of cyclone occurrence). Serial cyclones are clustered in time and are associated with large economic losses in Europe. Cyclone variability and seriality are intimately linked to the low frequency variability. To have a realistic representation of high and mid‐latitude regional climate in general circulation mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
(58 reference statements)
0
12
0
Order By: Relevance
“…Clusters of extratropical cyclones can result in economic losses comparable to those of a US hurricane and, due to the structure of reinsurance contracts, a cluster of events can cost more than a single event with the same total loss (Vitolo et al , ). Climate models have been shown to underestimate clustering (Kvamstø et al , ) and the physical drivers of clustering remains an active area of ongoing research (e.g. Hanley and Caballero, ; Neu et al , ; Pinto et al , ; Blender et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Clusters of extratropical cyclones can result in economic losses comparable to those of a US hurricane and, due to the structure of reinsurance contracts, a cluster of events can cost more than a single event with the same total loss (Vitolo et al , ). Climate models have been shown to underestimate clustering (Kvamstø et al , ) and the physical drivers of clustering remains an active area of ongoing research (e.g. Hanley and Caballero, ; Neu et al , ; Pinto et al , ; Blender et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests we cannot gain the benefits of smaller sampling errors from long integrations of the ECHAM5 climate model at the present time, due to its inability to simulate observed stronger clustering of more severe storms. Kvamsto et al (2008) note significant differences in clustering between a different climate model and observations, though β versus storm severity is not analysed. These two studies suggest climate models have different clustering behaviour from observed; however, they represent a small sample, and analysis of more climate models is needed to make firmer, useful conclusions on climate models' quality of clustering simulations.…”
Section: Resultsmentioning
confidence: 99%
“…However, previous studies find significant differences between climate models and observed behaviour (e.g. Kvamsto et al, 2008, and the underestimate of clustering for most severe storms in Tables 3a and b of Karremann et al, 2014a). New research by Pinto et al (2014) looks for the underlying mechanisms generating the cyclone families and persistent climate states that produce severe clusters on seasonal timescales.…”
Section: S Cusack: the Observed Clustering Of Damaging Extratropicalmentioning
confidence: 99%
“…The I d is a measure of the normal variability of intervals between storm peaks and is the quantity (with time dimension) defined as the ratio of the variance ( ΔT − ⟨ ΔT ⟩) 2 of the time interval ΔT between storm peaks to the mean interval ⟨ ΔT ⟩. The method itself is not innovative, because it has been applied by other authors (Mailier et al ., ; Kvamstø et al ., ; Vitolo et al ., ) in different contexts and using different approaches. However, the way the method has been employed here differs from previous work.…”
Section: Methodsmentioning
confidence: 99%
“…Several techniques to identify groups of cyclones have been implemented, such as a Bayesian approach (Fawcett and Walshaw, 2008), a running sum of daily cyclone counts e402 V. A. GODOI et al (Pinto et al, 2014), and the calculation of a dispersion statistic based on the Poisson process and cyclone counts (Mailier et al, 2006;Kvamstø et al, 2008;Vitolo et al, 2009). Studying cyclone clusters, however, does not necessarily provide useful information on the formation of SWCs.…”
Section: Introductionmentioning
confidence: 99%